Heart rate variability modifications in response to different types of exercise training in athletes - Perrone, M. A.; Volterrani, M.; Manzi, V.; Barchiesi, F.; Iellamo, F. (The Journal of Sports Medicine and Physical Fitness, 2021)
Spectral analysis of heart rate variability (HRV) is a long-standing technique to indirectly assess neural cardiac regulation. This article specifically addressed how spectral analysis of HRV could help to understand neural cardiovascular adaptations to long-term exercise training; and inform us on training status in athletes. We reviewed literature searching for articles investigating resting cardiovascular adaptations to long-term exercise training through spectral analysis of HRV in athletes, from amateur to world class categories, practicing different sport disciplines, and focusing, in particular, on a series of work performed over time in our laboratory, which may highlight how different types of exercise training differently affect neural cardiac regulation. Spectral analysis of HRV has been shown its capability of detecting different adaptational changes in cardiac autonomic nervous system (ANS) regulation attending physical training in athletes of different sport disciplines. Studies showed that spectral analysis of HRV provide results that are sport-dependent and differ at individual level. ANS adaptations to exercise training are presented and discussed. Reported studies indicate that spectral analysis of HRV is an effective tool to monitor and optimize the training process and to predict athletic achievements in competitions. Cardiac ANS adaptations are strongly dependant on the type of training being performed. The individual nature of cardiac ANS adaptations should be considered to properly interpret the observed findings.